Experimental Study on the Failure of Bamboo Laminated Hollow Section Beam-Column Joints using Glue-in-Rod Bracket - Arifin, Achmad Saiful; Karyadi, Karyadi; Nindyawati, Nindyawati (Reka Buana : Jurnal Ilmiah Teknik Sipil dan Teknik Kimia, 2023)
Building materials that emit pollutants, are non-renewable, and generate environmental waste require attention. Wood, a popular and natural material, is facing increasing scarcity, necessitating a substitute. Laminated bamboo emerges as the most akin and natural alternative to wood. Research into laminated bamboo encompasses diverse cross-sections, joint types, and field applications, demanding further investigation.This study aimed to ascertain failure types and damage patterns in laminated bamboo hollow section beam-column joints modified with glue-in rod-bracket connections, using petung bamboo (dendrocalamus asper). The research employed an experimental approach with descriptive analysis. Joint failures were evaluated based on moment-rotation relationships within prescribed rotational limits per standards, while joint damage was assessed through visual inspection of joint components.The study's dependent variables included thread rod diameters of 6 mm, 8 mm, dan 10 mm, and 4 dan 6 embedded thread rods, while the independent variables were failure types and joint collapses. Results revealed serviceability failures in samples 8.6, 10.4, and 10.6. Joint damage across all test specimens primarily manifested as broken thread rods. The highest joint strength observed was 6.28 kNm in sample 10.6, with the lowest at 2.25 kNm in sample 6.4.Based on the findings, increasing thread rod diameters to achieve ductile joints resulted in longer rotations but did not meet the planned strength due to bracket-induced prying effects causing bolt head failure. Despite this, the collapse type aligned with the research plan. Addressing the bracket's fulcrum effect during field applications requires solutions, potentially involving enlarging the bracket's base and increasing the number of thread rod points. The tests did not damage the laminated bamboo components, emphasizing the need to consider laminated bamboo cross-sectional dimensions and thread rod fulcrum effects in subsequent tests to ensure uniform component performance.